The role of protein quality control in mitochondrial protein homeostasis under oxidative stress - Bender, Tom; Leidhold, Claudia; Ruppert, Thomas; Franken, Sebastian; Voos, Wolfgang (Proteomics, 2010)
Mitochondria contribute significantly to the cellular production of ROS. The deleterious effects of increased ROS levels have been implicated in a wide variety of pathological reactions. Apart from a direct detoxification of ROS molecules, protein quality control mechanisms are thought to protect protein functions in the presence of elevated ROS levels. The reactivities of molecular chaperones and proteases remove damaged polypeptides, maintaining enzyme activities, thereby contributing to cellular survival both under normal and stress conditions. We characterized the impact of oxidative stress on mitochondrial protein homeostasis by performing a proteomic analysis of isolated yeast mitochondria, determining the changes in protein abundance after ROS treatments. We identified a set of mitochondrial proteins as substrates of ROS-dependent proteolysis. Enzymes containing oxidation-sensitive prosthetic groups like iron/sulfur clusters represented major targets of stress-dependent degradation. We found that several proteins involved in ROS detoxification were also affected. We identified the ATP-dependent protease Pim1/LON as a major factor in the degradation of ROS-modified soluble polypeptides localized in the matrix compartment. As Pim1/LON expression was induced significantly under ROS treatment, we propose that this protease system performs a crucial protective function under oxidative stress conditions.